EXAMINING VARIABILITY: A GENRE ANALYSIS OF ENGLISH LANGUAGE EDUCATION STUDENTS' THESIS ABSTRACTS - Mustaqim, Muhammad Haris; Zuhra, Intan (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2023)
The abstract of the thesis is the initial segment that researchers scrutinize to ascertain its pertinence to their interests. Researchers must possess an inherent comprehension of the section's rhetorical progression, structure, and arrangement. This study investigates the genre of thesis abstract sections produced by undergraduate students from Aceh who are majoring in English Education. The writers are interested in examining the writing style of Acehnese undergraduate students when composing their thesis abstracts. The dataset utilized in this study comprises 50 specifically chosen thesis abstracts from 5 universities in Aceh. The data analysis utilizes Hyland's five-move structural model of the abstract section, as well as the status of the motions as described by Huttner. The findings indicate that Hyland's five-move structure model is a useful tool for examining the move structure of the abstract section. Furthermore, there is no notable variation in the move structures across all datasets. The moves that occur most frequently are move 2, move 3, and move 4, making them the mandatory moves. The results could assist English as a Foreign Language (EFL) instructors in instructing and preparing their students to write the abstract section. Additionally, it could enhance the effectiveness of EFL students in composing well-organized abstract sections and improve researchers' understanding and sensitivity while crafting their thesis abstracts